Pelestarian Tradisi Malam Nujuh Likur melalui Kegiatan Pengabdian Masyarakat di Desa Taba Terunjam, Bengkulu Tengah: Penelitian - Iva Mutiara; Nanda Sulastri; Nagita Kasi Anggelia; Fatih Aldi Wahyudi4; Dewi Maulana; Panca Oktoberi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesia is known as a country with extraordinary cultural richness. One form of local cultural heritage that is still preserved in Bengkulu Province is the Malam Nujuh Likur tradition, which is celebrated every 27th night of Ramadan. This tradition reflects spiritual values, mutual cooperation, and kinship through lighting colok lamps and other religious activities. This study aims to explore the role of Real Work Lecture (KKN) students of the State Islamic University (UIN) Fatmawati Sukarno Bengkulu in preserving this tradition in Taba Terunjam Village. The study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that KKN students act as agents of cultural preservation through educational programs, such as cultural socialization, religious competitions, making colok lamps, and Islamic studies. The active involvement of students is able to arouse community participation, especially the younger generation, in maintaining and internalizing local and religious values. This study emphasizes the importance of synergy between universities and the community in efforts to preserve local wisdom in a participatory and sustainable manner.